2021
DOI: 10.1158/0008-5472.can-20-2426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FGFR Reactivates IFNγ Signaling in Tumor Cells to Enhance the Combined Antitumor Activity of Lenvatinib with Anti-PD-1 Antibodies

Abstract: Combination therapies consisting of immune checkpoint inhibitors plus anti-VEGF therapy show enhanced antitumor activity and are approved treatments for patients with renal cell carcinoma (RCC). The immunosuppressive roles of VEGF in the tumor microenvironment are well studied, but those of FGF/FGFR signaling remain largely unknown. Lenvatinib is a receptor tyrosine kinase inhibitor that targets both VEGFR and FGFR. Here, we examine the antitumor activity of anti-PD-1 mAb combined with either lenvatinib or axi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 56 publications
2
80
0
Order By: Relevance
“…Further research results showed that epi-PCGs had more transcripts and exons than non-epi-PCGs, but the transcript length was relatively short, indicating that although epi-PCGs accounted for a relatively small proportion, it is possible that the level of transcription protein was decreased. These epi-PCG-related pathways include “bladder cancer”, “hematopoietic cell lineage” ( 49 51 ), and “JAK-STAT signaling pathway” ( 52 54 ), which are related to tumor progression, indicating that these epi-PCGs play a pivotal role in the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Further research results showed that epi-PCGs had more transcripts and exons than non-epi-PCGs, but the transcript length was relatively short, indicating that although epi-PCGs accounted for a relatively small proportion, it is possible that the level of transcription protein was decreased. These epi-PCG-related pathways include “bladder cancer”, “hematopoietic cell lineage” ( 49 51 ), and “JAK-STAT signaling pathway” ( 52 54 ), which are related to tumor progression, indicating that these epi-PCGs play a pivotal role in the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…After preprocessing, 80 and 63 UM samples remained in TCGA and GSE22138 cohorts, respectively ( Tables S1, S2 ). Limma R package ( 18 , 19 ) was used to normalize the quantile of gene expression data.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is critical to identify more effective immunotherapy targets and predictive biomarkers. Previous experiments have found that FGFR is associated with immunity ( 17 , 18 ), but the correlation between FGFR protein expression and tumor-infiltrating immune cells is not clear. In addition, the underlying mechanism how FGFRs regulates the immune environment and their association with the efficiency of immunotherapy remains unclear.…”
Section: Introductionmentioning
confidence: 94%